A co-designed integrated kidney and diabetes model of care improves mortality, glycaemic control and self-care. Issue 8 (26th July 2021) - Zimbudzi, Edward; Lo, Clement; Ranasinha, Sanjeeva; Earnest, Arul; Teede, Helena; Usherwood, Tim; Polkinghorne, Kevan R; Fulcher, Gregory; Gallagher, Martin; Jan, Stephen; Cass, Alan; Walker, Rowan; et al.
ABSTRACT: Background: Current healthcare models are ill-equipped for managing people with diabetes and chronic kidney disease (CKD). We evaluated the impact of a new diabetes and kidney disease service (DKS) on hospitalization, mortality, clinical and patient-relevant outcomes. Methods: Longitudinal analyses of adult patients with diabetes and CKD (Stages 3a–5) were performed using outpatient and hospitalization data from January 2015 to October 2018. Data were handled according to whether patients received the DKS intervention ( n  = 196) or standard care ( n  = 7511). The DKS provided patient-centred, coordinated multidisciplinary assessment and management of patients. Primary analyses examined hospitalization and mortality rates between the two groups. Secondary analyses evaluated the impact of the DKS on clinical target attainment, changes in estimated glomerular filtration rate (eGFR), glycated haemoglobin A1c (HbA1c), self-care and patient activation at 12 months. Results: Patients who received the intervention had a higher hospitalization rate {incidence rate ratio [IRR] 1.20 [95% confidence interval (CI) 1.13–1.30]; P < 0.0001}, shorter median length of stay {2 days [interquartile range (IQR) 1–6] versus 4 days [IQR 1–9]; P < 0.0001} and lower all-cause mortality rate [IRR 0.4 (95% CI 0.29–0.64); P < 0.0001] than those who received standard care. Improvements in overall self-care [mean difference 2.26 (95% CI 0.83–3.69); P < 0.001] and in statin use and eye and feet examinations were observed. The mean eGFR did not change significantly after 12 months [mean difference 1.30 mL/min/1.73 m 2 (95% CI −4.17–1.67); P = 0.40]. HbA1c levels significantly decreased by 0.40, 0.35, 0.34 and 0.23% at 3, 6, 9 and 12 months of follow-up, respectively. Conclusions: A co-designed, person-centred integrated model of care improved all-cause mortality, kidney function, glycaemic control and self-care for patients with diabetes and CKD. Graphical Abstract: